2005
DOI: 10.1510/icvts.2005.107128
|View full text |Cite
|
Sign up to set email alerts
|

Internal mammary revascularization in patients with variant angina and normal coronary arteries

Abstract: Patients with variant angina refractory to medical therapy pose a difficult management problem. In patients with discrete obstructive lesions, coronary revascularization may be helpful. However, it has been widely accepted that coronary revascularization is contraindicated in patients with isolated coronary spasm without evidence of obstructive disease. Here we describe the two patients with life-threatening, medically intractable Prinzmetal's angina and angiographically normal coronary arteries, both of whom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 5 publications
0
27
0
1
Order By: Relevance
“…12 Coronary angioplasty performed in CAS patients produced results similar to those without variant angina. 13 Life-threatening ventricular arrhythmias in CAS were the reason for automatic defibrillator implantation 14 (Table 3).…”
Section: Therapies Established and Newmentioning
confidence: 96%
“…12 Coronary angioplasty performed in CAS patients produced results similar to those without variant angina. 13 Life-threatening ventricular arrhythmias in CAS were the reason for automatic defibrillator implantation 14 (Table 3).…”
Section: Therapies Established and Newmentioning
confidence: 96%
“…Ono et al [55], on the other hand, have reported extremely good clinical results with a pedicled in situ internal mammary artery graft in two patients with intractable variant angina refractory to medical management. Both patients had isolated coronary artery spasm on angiography.…”
Section: Coronary Artery Bypass Graftingmentioning
confidence: 99%
“…Atherosclerotic disease affecting large coronary arteries altered their vasomotor tone and reactivity [9,31,[52][53][54][55]. There was an intimate association of spasm with sites of organic stenosis.…”
Section: Abnormal Vasomotor Tone (Spasm Of the Coronary Arteries)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported new cases of coronary spasm following implantation of a drug-eluting stent (69,70); thus, coronary stents should be selected very carefully for patients with CSA. Furthermore, there are two reported cases of medically refractory CSA without signifi cant coronary stenosis who underwent coronary aorta bypass grafting (CABG) with the internal mammary artery (66). The postoperative course was uneventful, but spasticity remained in the other vessels (20).…”
Section: Non-pharmacological Treatment For Medically Refractory Coronmentioning
confidence: 99%